The Mediating Role of Organizational Identification in the Relation between Organizational Social Capital, Perceived Organizational Prestige, Perceived Employability and Career Satisfaction. (8th April 2021) - Peña-González, Karina; Nazar, Gabriela; Alcover, Carlos-María
Abstract: In career development, a variety of personal, organizational and labor market variables challenge employees and organizations, in particular those in dynamic working environments, such as higher education (HE) institutions. This study examines the association between work history, organizational social capital (OSC) and perceived organizational prestige (POP) as antecedent variables, and perceived employability (PE) and career satisfaction (CS) as outcome variables, as well as the mediating role of organizational identification (OI) in these relations. A sample of 283 workers in Chilean HE institutions filled out an on-line questionnaire, and hypotheses were tested using a mediation model. Results indicated a significant mediation effect of OI, abt = 0.363, 95% CI [0.181, 0.576] abt /c = 31.98%, to explain the relationship between internal perceived employability (IPE) and its predictor variables POP, abpo = 0.102, 95% CI [0.056, 0.160], abpo /c = 9.01%, and OSC, abcsoc = 0.101, 95% CI [0.053, 0.183, abcsoc /c = 8.89%. Promoting a positive image of the organization and its social capital, strengthened by OI, emerge as strategies for HR management oriented toward workers' career development, with consequent implications for commitment, intention to leave and ultimately for organizational results. The study provides a deeper understanding of the complexity of careers and explains the importance of identification with the organization when the impact of organizational attributes on one's career is analyzed.